2021
DOI: 10.1111/aos.14905
|View full text |Cite
|
Sign up to set email alerts
|

The role of retinal fluid location in atrophy and fibrosis evolution of patients with neovascular age‐related macular degeneration long‐term treated in real world

Abstract: To assess the effect of clinical factors on the development and progression of atrophy and fibrosis in patients with neovascular age-related macular degeneration (nAMD) receiving long-term treatment in the real world.Methods: An ambispective 36-month multicentre study, involving 359 nAMD patients from 17 Spanish hospitals treated according to the Spanish Vitreoretinal Society guidelines, was designed. The influence of demographic and clinical factors, including the presence and location of retinal fluid, on be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…Similar to our results, other studies have also showed that presence of SRF does not impact VA outcomes significantly (Kim et al, 2021; Maguire et al, 2016). Some recent studies have even found that functional outcome is improved in cases with persistent subretinal fluid, and that the presence of SRF could even reduce the occurrence of atrophy and fibrosis (Llorente‐Gonzalez et al, 2021; Zarbin et al, 2021). It has been suggested that SRF might have a neuroprotective effect, potentially by providing a fluid buffer, between the MNV and the outer segments of the photoreceptors or by separating photoreceptor cells from toxicity by direct contact to suffering retinal pigment epithelium cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our results, other studies have also showed that presence of SRF does not impact VA outcomes significantly (Kim et al, 2021; Maguire et al, 2016). Some recent studies have even found that functional outcome is improved in cases with persistent subretinal fluid, and that the presence of SRF could even reduce the occurrence of atrophy and fibrosis (Llorente‐Gonzalez et al, 2021; Zarbin et al, 2021). It has been suggested that SRF might have a neuroprotective effect, potentially by providing a fluid buffer, between the MNV and the outer segments of the photoreceptors or by separating photoreceptor cells from toxicity by direct contact to suffering retinal pigment epithelium cells.…”
Section: Discussionmentioning
confidence: 99%
“… 59 , 60 On the other hand, fibrosis as a result of retinal remodeling processes might not respond to anti-VEGF therapy. 58 , 61 Fibrosis is furthermore associated with worse visual outcomes and overlaying photoreceptor degeneration. Fibrosis might therefore be as important as the development of macular atrophy as disease progresses, with photoreceptor degeneration as the common cause for vision loss.…”
Section: Fluid Quantificationsmentioning
confidence: 99%
“…The presence of SRF halves the probability of MA developing within a wAMD lesion [45] and in the HARBOR trial, SRF was associated with a lower risk of MA incidence over 24 months [27]. SRF thickness of >25 μm is significantly associated with a lower risk of MA development ( p < 0.001) and its presence has generally been associated with slower progression of atrophy and better visual outcomes [37, 43, 128]. Patients with wAMD whose phenotype derives from SRF alone show low rates of MA development over a 5-year follow-up period, despite 96.2% of eyes showing drusen, a hallmark precursor of MA.…”
Section: Potential Protective Factorsmentioning
confidence: 99%